2015
DOI: 10.1155/2015/250201
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Variability Assessed by Continuous Glucose Monitoring and Short-Term Outcome in Diabetic Patients Undergoing Percutaneous Coronary Intervention: An Observational Pilot Study

Abstract: Poor glycemic control is associated with unfavorable outcome in patients undergoing percutaneous coronary intervention (PCI), irrespective of diabetes mellitus. However a complete assessment of glycemic status may not be fully described by glycated hemoglobin or fasting blood glucose levels, whereas daily glycemic fluctuations may influence cardiovascular risk and have even more deleterious effects than sustained hyperglycemia. Thus, this paper investigated the effectiveness of a continuous glucose monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Consequently, several studies described the clinical impact of GV in patients with coronary artery disease undergoing PCI [1416]. A high MAGE value has been demonstrated an independent predictor of long-term poor prognosis in a large cohort of patients with acute coronary syndromes undergoing coronary stenting [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, several studies described the clinical impact of GV in patients with coronary artery disease undergoing PCI [1416]. A high MAGE value has been demonstrated an independent predictor of long-term poor prognosis in a large cohort of patients with acute coronary syndromes undergoing coronary stenting [15].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high levels of GV, assessed by continuous glucose monitoring (CGM), appear to have even more deleterious effects than sustained hyperglycaemia in the pathogenesis of cardiovascular autonomic neuropathy and other cardiovascular complications [12, 13]. Previous studies have already correlated an increased GV to the occurrence of adverse events in patients with acute coronary syndromes undergoing percutaneous coronary revascularization (PCI) [1416]. Finally, critically ill patients admitted to intensive care unit with high GV have shown a significant increased mortality compared with those with less glycemic variability even with slight hyperglycaemia [17].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these data, it has been speculated that myocardial injury could be primarily influenced by hypoglycemia and by rapid glycaemic spikes, whereas the kidney may be mainly susceptible to slower and longer hyperglycaemic excursions. 69 Kuroda et al also observed that MAGEs strongly correlated with neo-intimal growth after stenting, evaluated by optimal coherence tomography, in patients with CAD. 12 In conclusion, the relationship between GV and CV outcome is still a subject of research and debate; however, to date the majority of the evidences collected suggests that we may include GV in the list of potential risk factors for the development of cardiac complications in both diabetic and not diabetic patients.…”
Section: Pathophysiological Mechanisms Relating Gv and CV Complicatmentioning
confidence: 90%
“…In a series of patients treated with elective coronary stenting, a significant correlation between GV and renal and myocardial damage was found, measured by serum creatinine, neutrophil gelatinase-associated lipocalin, and troponin-I levels, supporting the idea that an optimal glycaemic control should be achieved in order to prevent complications and improve outcome also in the setting of PCI. 69 Notably, increased MAGE-up values, predominantly indicating hyperglycaemic peaks, are observed in patients with higher post-procedural creatinine and neutrophil gelatinase-associated lipocalin variations, whereas, a significant correlation after coronary stenting was found between MAGEdown, indicating hypoglycaemic nadirs, and troponin release. Based on these data, it has been speculated that myocardial injury could be primarily influenced by hypoglycemia and by rapid glycaemic spikes, whereas the kidney may be mainly susceptible to slower and longer hyperglycaemic excursions.…”
Section: Pathophysiological Mechanisms Relating Gv and CV Complicatmentioning
confidence: 91%
See 1 more Smart Citation